Epidemiological survey of cases of exogenous poisoning in Imperatriz-MA, 2018-2022 (Research, Society and Development, 2023)
Objective: To know the reality of the city of Imperatriz-MA regarding the epidemiological profile of patients who suffered exogenous intoxication in the years 2018-2022, to set goals to combat and prevent it. Methods: This is a descriptive, retrospective study, with a quantitative approach, whose search took place from April to May 2023, using public databases, through TABNET, an application of the Department of Informatics of the Unified Health System ( DATASUS). Results: The exogenous intoxication in the city of Imperatriz-MA had as the main toxic agent the medicines of familiar use, being the accidental use and the attempt of self-extermination, the circumstances most involved in the episodes. Conclusion: From the epidemiological description, it is possible to establish health actions as a way to prevent accidental cases. In addition, multidisciplinary care related to mental health is extremely important in order to combat suicide attempts, directly influencing the incidence of intoxicated patients.